2012
DOI: 10.1177/1329878x1214200115
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of Integration in the Australian Press Coverage of Muslims: Implications for Social Inclusion and Exclusion

Abstract: This article uses a framing perspective to analyse the Australian press coverage of Muslim Australians with regard to the issue of their integration into Australian society. Taking a qualitative approach, this study is based on analysis of articles published in The Australian, the Sydney Morning Herald, The Age and the Courier-Mail in alternate years from 2002 to 2010. Of particular focus are the themes and definitions associated with integration that arise in the context of the coverage. The study finds the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The general public tends to rely on news media for information about asylum seekers; in turn, the media’s framing of these issues, by selecting events, opinions, facts, images and information, shapes audience responses, encouraging ‘particular interpretations or understanding of issues’ and reflecting, increasing and influencing prejudicial attitudes (Hodgetts and Chamberlain, 2013; McHugh-Dillon, 2015; Rane and Hersi, 2011: 138). Through shaping and amplifying public attitudes, the media has an impact on policy outcomes by influencing government considerations and communication of issues (Branton and Dunaway, 2008; Hericourt and Spielvogel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The general public tends to rely on news media for information about asylum seekers; in turn, the media’s framing of these issues, by selecting events, opinions, facts, images and information, shapes audience responses, encouraging ‘particular interpretations or understanding of issues’ and reflecting, increasing and influencing prejudicial attitudes (Hodgetts and Chamberlain, 2013; McHugh-Dillon, 2015; Rane and Hersi, 2011: 138). Through shaping and amplifying public attitudes, the media has an impact on policy outcomes by influencing government considerations and communication of issues (Branton and Dunaway, 2008; Hericourt and Spielvogel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(2015) reported that almost 80 percent of survey participants (a cross section of the Australian population) expressed the view that media portrayals of Muslims in Australia were unfair, and the same proportion of respondents thought that media reports impacted on non‐Muslims’ views of Muslims. A study of 290 newspaper articles over a ten‐year period, conducted by Rane and Hersi (2012), found that Australian media coverage framed Muslims mostly in terms of “radicalization” and terrorism and that their integration was usually juxtaposed with concepts such as “Australian values,” “citizenship” and “extremism.” Biased portrayals of their community and/or religion led Muslims to mistrust and fear media coverage, and to feel angry about misrepresentation and stigmatization of Islam and Muslims (Cherney and Murphy 2016; Ewart, Pearson, and Healy 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There in an overwhelming concern regarding the media, as it is not viewed as trustworthy (Rane & Hersi, 2012). There has been a large number of negative stories about Muslims in the media since 2000; This is a consequence of tragic events, such as a gang rape of woman in Sydney by Muslim men, insensitive comments by someone claiming to be a Muslim leader, and the Cronulla riots (Bouma, 2011;Dunn, Klocher, & Salabey, 2007); media reports on Muslims have similarly worsened after international and national terror attacks.…”
Section: Acculturative Stressmentioning
confidence: 99%